Submicron sea spray fluxes: - Geever, M.; O'Dowd, C.D.; Ekeren, S. van; Flanagan, R.; Nilsson, E.D.; Leeuw, G. de; Rannik, U. (2005)
Eddy covariance aerosol flux measurements were conducted at the Mace Head coastal station in the North East Atlantic. Footprint and micrometeorological analysis under clean marine air mass conditions indicated that fluxes representative of open ocean conditions could be derived during high tide conditions and an oceanic fetch. Sea-spray fluxes were derived for total particle sizes larger than 10 nm and total particle sizes larger than 100 nm (i.e. covering the Aitken and Accumulation mode). The source fluxes (F) were found to be strongly correlated with both wind speed (U) and friction velocity (u*), following, by convention, an exponential relationship (Log F = a U + c) relationship. Comparison of source fluxes at sizes larger than 10 nm and larger than 100 nm demonstrates that approximately 50% of the number flux can be attributed to the accumulation mode and 50% to the Aitken mode. At 10 ms-1 wind speeds, the total primary marine aerosol flux is of the order of 2 × 106 m-2 s-1, increasing to 20 × 106 m-2 s-1 at 20 ms-1. Copyright 2005 by the American Geophysical Union.